Green capital East of the Leitha? The chances and disadvantages of major cities in the Pannonian Basin to win the European Green Capital Award - Dalma Schmeller; Gábor Pirisi (Hungarian Geographical Bulletin, 2023)
This study focuses on the chances of major cities (over 100,000 inhabitants) in the Pannonian Basin to win the European Green Capital Award. The 28 cities covered by the analysis can be divided into two groups: eleven cities that have already applied (one of them, Ljubljana was a previous winner) and seventeen cities that have not yet applied for the award. During the research, we divided the cities according to these two groups. In the study we applied various statistical and spatial analysis methods to capture similarities and differences in their environmental indicators. The results show that there are no significant differences in environmental indices between these two groups, and the values of the 2016 winner city (Ljubljana) are most similar to Austrian, Slovenian, and Croatian cities. Furthermore, based on the results of the similarity search, it can be stated that the further east we go, the less similar the examined cities are to Ljubljana. We also examined the probability of reaching the finals, indicating that cities that have not yet applied have a low likelihood of winning the award.